50 trade secrets of great design : packaging - Cliff, Stafford (Gloucester, Mass. : Rockport Pubr, 1999)
"Product packaging design today offers contemporary designers the opportunity to work with new methods and materials of construction that allow fresh and exciting ideas, and yet they are more than ever constrained by the most conventional of restrictions, such as low budgets, unimaginative briefs, and consumer research. Fifty packaging projects are selected from a global survey of this prolific industry and analyzed and discussed individually, tracing the challenges and problems facing some of today's very best designers."--Jacket
-- Vosene -- Maggie Beer -- Halfords -- Calbert's Cocktail Mix -- Lucozade NRG -- Travelight -- Beantown Soup Company -- Boots Herbal -- Bend in the River -- Hydro -- Frutte -- Mondeo -- Boots Aromatherapy -- Chivas Brothers -- Superga -- Alta -- Virgin Vie -- Black Wattle -- Whittard -- Boston Acoustics -- Gleneagles -- Carluccio's -- Premium Lehmann Wines -- The Bath Hosue Limited -- Starbucks Frappaccino -- Tony's Freezer Cocktails -- Barletts Wines -- Boaters -- Sparkling Ice -- W.H. Smith Stationery -- Dewars -- Conran Collection -- Crabtree and Evelyn -- Heals -- Nikon -- Secret Weapon -- Ballantine Purity -- Bond, James Bond -- Fedrigoni -- Kyusu -- Sun Essentials -- Monsoon -- Remington -- BP Visco -- Seattle Coffee -- Superdrug Multi Vitamins -- Joy -- Fabris Lane -- Chocca Mocca -- Giro
Keywords: Packaging -- Design; Commercial art; Designers